Diseño de un mecanismo de sustitución de trigo importado por el fomento de la producción nacional de un producto alternativo estudio de caso Harina de Banano en el período 2008-2012 - Ortuño Pardo, Marlon Sebastián (2015)
This research establishes a mechanism of partial substitution of wheat imported by using part of a domestic product such as the banana integrates data from background research such as problematic, justification and objectives, which gives the guideline for development. Data development refers to the use of theoretical basis used in the study, so that for this we have cited several authors who through their work have obtained relevant to the present research data; likewise referred to legal guideline to which the research topic is held. Presents the methodology used in the research design, population and sample used, the questionnaire used for gathering information and processing and analysis of this information, based on which has been able to obtain a diagnosis of the current use of wheat flour and possible substitution with banana flour. Refers to both national and international levels, exports and imports of wheat and banana, and general information that sets the tone for the capacity that is used internally for banana as raw material for flour and use the baking industry. Quantifiably demonstrates the economic benefits that could be obtained through partial substitution of wheat flour, both generally and in terms of the baking industry, and the process is identified for industrial scale production of the flour.